Evaluation of microplastics ingested by sea cucumber holothuria scabra from Pulau Jambongan, Sabah - Sarah Syazwani Shukhairi; Nurzafrah Mazlan; Vijay Kumar Subbiah (Springer Verlag, 2025)
Microplastics (MPs) are tiny plastic pieces having a diameter of less than 5 mm. They can arise from larger plastic debris that degrades over time, synthetic fibres from clothing, microbeads in personal care items and even larger plastic debris. Sea cucumbers are marine creatures vital to the ocean's ecosystem as they assist in maintaining a clean seabed and recycle nutrients. The aim of this research was to characterize the types of MPs isolated from the sea cucumber Holothuria scabra from Pulau Jambongan, Sabah. A total of 30 H. scabra were collected. Their gastrointestinal tracts were removed and digested using NaOH. The digestates were filtrated several times to extract the MPs. MPs were observed under microscope and categorized into shapes and colours. To determine the functional group of polymers, further analysis using Fourier Transform-Infrared Spectroscopy (FTIR) was performed. The samples contained a total of 7403 MPs. Majority of MPs were black colored (72.25%) and in the form of fibres (99.05%). Two types of polymers were detected: polycarbonate (PC) found in 4% of the population and polymethyl methacrylate (PMMA) present in 96%. In conclusion, the presence of MPs in the gastrointestinal tract of H. scabra suggests that the animals and their habitat have been contaminated. Further study is required to comprehend the effects of MPs on sea cucumbers and other marine organisms as well as to develop prevention strategies.